(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the outcomes of cleft palate repair using the double opposing Z-plasty technique (Furlow palatoplasty). Methods: A combined retrospective and prospective descriptive study without a control group was conducted on 30 patients with cleft palate who underwent repair using the double opposing Z-plasty technique. Postoperative outcomes were assessed in terms of anatomical closure, speech function, and complications. Results: All patients achieved complete wound healing (100%) with no recorded postoperative complications; 80% of patients showed significant improvement in hypernasality and reduced nasal air emission following surgery. Conclusion: The double opposing Z-plasty technique is an effective method that yields good results in cleft palate treatment. It improves both anatomical and speech outcomes for patients.